Development of Guided Inquiry-Based Student Worksheets on the Concept of Classification of Living Organisms to Train Students Science Process Skills - Padliah, Siti; Sjaifuddin, Sjaifuddin; Alamsyah, Trian Pamungkas (Jurnal Pijar Mipa, 2025)
Science learning in schools should not only emphasize conceptual understanding but also foster science process skills that train critical thinking, analytical reasoning, and problem-solving abilities. However, classroom practice is still dominated by rote memorization, leaving students’ science process skills underdeveloped. This study addresses the gap by developing a Guided Inquiry-based Student Worksheet on the concept of living things classification. The unique contribution of this student worksheet lies in its integration of guided inquiry phases with authentic classification activities, enabling students to engage in exploration, observation, and independent analysis. Unlike conventional worksheets that mainly provide summaries or drill questions, this product is designed to stimulate scientific investigation and active participation. The research adopted the 4D development model (Define, Design, Develop, Disseminate), although this study was limited to the Develop stage. Nine validators (three media experts, three material experts, and three science teachers) and 35 seventh-grade students participated as respondents. Validation results indicated an average feasibility score of 86.9% (“highly feasible”), while student responses reached 87.2% (“very positive”). These findings confirm that the developed student worksheet is not only valid in terms of content and presentation but also well-received by students. Beyond providing an alternative learning material, the broader implication of this study is that Guided Inquiry-based student worksheet can serve as a strategic tool to cultivate science process skills by combining discovery learning with real-life classification practices. Consequently, this product has the potential to enrich science learning with more meaningful and activity-oriented approaches, while preparing students to face 21st-century challenges that demand critical thinking, collaboration, and evidence-based reasoning.